2015
DOI: 10.1007/s10157-015-1142-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eculizumab in childhood atypical hemolytic uremic syndrome in Japan

Abstract: Eculizumab is efficacious and well-tolerated therapy for children with aHUS. Although pathogenic mutations could not be detected in five patients, all patients showed immediate normalization of hematological abnormalities, strongly suggesting complement-related aHUS. This prompt hematological amelioration can become an indicator for therapeutic efficacy of eculizumab. However, appropriate indications and optimal duration of the treatment remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…Few retrospective and prospective clinical studies have evaluated the safety and efficacy of eculizumab in Japanese patients with aHUS [5,6,[14][15][16][17]. The outcomes in this aHUS cohort [11].…”
Section: Discussionmentioning
confidence: 99%
“…Few retrospective and prospective clinical studies have evaluated the safety and efficacy of eculizumab in Japanese patients with aHUS [5,6,[14][15][16][17]. The outcomes in this aHUS cohort [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent case published by Fukui et al [19] describes a case with TMA and EGPA and TMA history has been reported in pediatric patients with aHUS [20]. Therefore, considering all the facts, it might be possible that a relationship between EGPA and aHUS exists.…”
Section: Discussionmentioning
confidence: 89%
“…The authors wish to thank Mr. James Robert Valera of Redact Editing and Translation Services for his help in editing this manuscript. The information for Patients 1–3 was submitted to the Japanese National Survey of Eculizumab for aHUS . The pathological findings in Case 2 have also been reported elsewhere …”
Section: Acknowledgmentsmentioning
confidence: 99%